Meta-analysis reveals that fisheries co-management alters socio-economic outcomes and resource well-being - Mike Fowler (Marine Ecology Progress Series, 2018)
Over half a century of governing efforts have failed to prevent the depletion of fish stocks around the globe. Ineffective management of over-exploited resources has resulted in a lack of willingness to comply with regulatory systems, magnifying problems at a time when many of the world’s fisheries face increasing pressure or crisis. Co-management, the sharing of management responsibilities between government, fishermen’s organisations and other stakeholders, has been advocated as the solution to engaging stakeholders. However, an evidence base is required to assess whether co-management improves the sustainability of fisheries. Here, we used qualitative and, for the first time, quantitative meta-analyses to assess the outcomes of local fisheries co-management schemes around the globe, by asking: (1) does co-management improve the socio-economic and biological factors underpinning fisheries? (2) how do the characteristics of the most successful co-management structures compare to less successful structures? Data from multiple studies was extracted and measured against performance criteria through meta-analysis, assessing process (compliance, control, conflict, influence and participation) and outcome indicators (household income, access to resource, fish yield and resource well-being). Co-management has an overall positive influence on all but one of the process indicators (conflict; no significant effect), but a negative influence on access to resource and resource well-being. Case studies that reported positive outcomes possessed attributes such as government support, funding and dedicated project staff, indicating certain prerequisites are required to establish a successful co-management scheme, though data limitations restrict our ability to draw more general conclusions.